2019
DOI: 10.1021/acs.jpcb.9b00782
|View full text |Cite
|
Sign up to set email alerts
|

Crowding-Induced Elongated Conformation of Urea-Unfolded Apoazurin: Investigating the Role of Crowder Shape in Silico

Abstract: Here, we show by solution nuclear magnetic resonance measurements that the urea-unfolded protein apoazurin becomes elongated when the synthetic crowding agent dextran 20 is present, in contrast to the prediction from the macromolecular crowding effect based on the argument of volume exclusion. To explore the complex interactions beyond volume exclusion, we employed coarse-grained molecular dynamics simulations to explore the conformational ensemble of apoazurin in a box of monodisperse crowders under strong ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 66 publications
(155 reference statements)
3
24
0
Order By: Relevance
“…It was also observed that crowding conditions affect a protein structure, and a protein can even fold faster in an optimum concentration regime . Molecular crowders surrounding the protein in a cell have a high variability of sizes and shapes. , From a theoretical perspective, most computational and modeling studies assume molecular crowders similar to the protein size. , Such models allow an investigation in similar conditions found in vivo with a volume occupancy between 5% and 40%. , …”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that crowding conditions affect a protein structure, and a protein can even fold faster in an optimum concentration regime . Molecular crowders surrounding the protein in a cell have a high variability of sizes and shapes. , From a theoretical perspective, most computational and modeling studies assume molecular crowders similar to the protein size. , Such models allow an investigation in similar conditions found in vivo with a volume occupancy between 5% and 40%. , …”
Section: Introductionmentioning
confidence: 99%
“…The cytoplasm of cells such as Escherichia coli have a macromolecule concentration of up to 300-400 g/L, and 20-30% of the intracellular volume is occupied by macromolecules (9,10). Recent studies revealed that crowding affects protein stability (11)(12)(13)(14), folding (15,16), binding affinity (17,18), and catalysis (15,(19)(20)(21)(22)(23). Specifically, the size, structure, concentration, and chemical nature of crowding agents contribute to changes in stability, folding, conformational equilibrium, and catalysis when compared with dilute conditions (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that such models are likely oversimplified. The shape of the crowders and the way they interact can influence the effects that the crowders exert on the molecules (O'Brien et al, 2011; Kang et al, 2015; Chen and Zhao, 2019; Zegarra et al, 2019), including how crowding affects protein diffusion (Balbo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study (Zegarra et al, 2019), a set of crowders with different shapes was used to reproduce and explain an NMR experiment and show that the unfolded apoazurin protein becomes more extended upon addition of dextran crowders. In this work, spheres and spherocylinders of various lengths were used along with a CG protein model.…”
Section: Reduced Models Of Crowdersmentioning
confidence: 99%